Mathematical and statistical methods for actuarial sciences and finance : MAF 2018 - Corazza, Marco; Durban, Maria; Grane, Aurea; Perna, Cira.; Sibillo, Marilena (Cham : Springer, 2018)
This volume gathers selected peer-reviewed papers presented at the international conference "MAF 2016 - Mathematical and Statistical Methods for Actuarial Sciences and Finance", held in Paris (France) at the Université Paris-Dauphine from March 30 to April 1, 2016. The contributions highlight new ideas on mathematical and statistical methods in actuarial sciences and finance. The cooperation between mathematicians and statisticians working in insurance and finance is a very fruitful field, one that yields unique theoretical models and practical applications, as well as new insights in the discussion of problems of national and international interest. This volume is addressed to academicians, researchers, Ph.D. students and professionals.
Includes bibliographical references.
Description based on publisher-supplied MARC data.
Keywords: Econometrics; Mathematical optimization